2019
DOI: 10.1101/829077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formal string instrument training in a class setting enhances cognitive and sensorimotor development of primary school children

Abstract: This randomized controlled trial shows for the first time that focused musical instrumental practice as compared to traditional sensitization to music provokes robust cognitive and sensorimotor transfer effects. Over the last two years of primary school (10-12-year-old children), sixty-nine children received biweekly musical instruction by professional musicians within the regular school curriculum. The intervention group learned to play string instruments, whereas the control group, peers in parallel classes,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Despite the less than encouraging evidence, dozens of new experimental investigations have been carried out in recent years, including the two largest randomized control trials (RCTs) in this field (Aleman et al, 2017;Haywood et al, 2015). Once again, the claims about the effectiveness of music training have been inconsistent across studies (e.g., James et al, 2019;Lukács & Honbolygó, 2019;Nan et al, 2018). We thus ran a meta-analysis including both old and new experimental studies to establish (a) which claims are justified, (b) what are the sources of heterogeneity across studies, and (c) which of the theories predicting that music training enhances cognitive and academic skills are corroborated/refuted.…”
Section: The Present Meta-analysismentioning
confidence: 99%
“…Despite the less than encouraging evidence, dozens of new experimental investigations have been carried out in recent years, including the two largest randomized control trials (RCTs) in this field (Aleman et al, 2017;Haywood et al, 2015). Once again, the claims about the effectiveness of music training have been inconsistent across studies (e.g., James et al, 2019;Lukács & Honbolygó, 2019;Nan et al, 2018). We thus ran a meta-analysis including both old and new experimental studies to establish (a) which claims are justified, (b) what are the sources of heterogeneity across studies, and (c) which of the theories predicting that music training enhances cognitive and academic skills are corroborated/refuted.…”
Section: The Present Meta-analysismentioning
confidence: 99%
“…These structural differences are believed to indicate functional reorganization, which may be associated with benefits in certain cognitive functions for musically-trained individuals [12]. Studies in children have revealed cognitive advantages amongst those who have received musical training compared to those that did not [13][14][15][16]. For example, children in a 15-month musical intervention group saw greater improvements in overall cognitive performance compared to control groups of drama lessons and no intervention [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, children in a 15-month musical intervention group saw greater improvements in overall cognitive performance compared to control groups of drama lessons and no intervention [ 15 ]. Further, children in a two-year intensive musical instrument training program manifested broad cognitive benefits including working memory, attention, and processing speed compared to a musical listening and theory program control [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors are also very grateful to the children and their parents for their precious collaboration. This manuscript has been released as a Pre-Print at https://www.biorxiv.org/content/10.1101/829077v1 (James et al, 2019).…”
Section: Acknowledgmentsmentioning
confidence: 99%